The Implementation of Differentiated Instruction Based on Learning Styles to Improve Science Learning Outcomes of Eighth Grade Students at SMP Negeri 11 South Tangerang City - Ai Dawati (Educare: Journal Educational and Multimedia, 2025)
This classroom action research aimed to describe the implementation of differentiated instruction based on students' learning styles and to improve science learning outcomes among eighth-grade students at SMPN 11 South Tangerang. The instructional approach was designed to accommodate visual, auditory, and kinesthetic learning preferences. The results indicated a meaningful enhancement in students’ academic performance from the initial to the subsequent cycle. The overall class achievement showed noticeable progress, and the number of students meeting the learning objectives increased. Additionally, improvements were observed across all learning styles, with each group reaching a high level of mastery by the end of the intervention. These findings confirm that differentiated instruction tailored to learning styles is effective in promoting better science learning outcomes.